The Using Cognitive Academic Language Learning Approach (CALLA) for Reading Strategy Instructions to Young Learners - Rizki, Annisa Khairir (Interdisciplinary Explorations in Research Journal, 2023)
One of the most important areas of young learners strategy research is the employment of reading strategy for English as a foreign language (EFL) learners. Students who actively utilize their reading comprehension strategies can comprehend and recall more information from what they read, as well as improve their language proficiency. This paper describes Cognitive Academic Language Learning Approach (CALLA) that facilitates young learners to enhance their English reading comprehension. The writer reviewed many of research studies of reading strategy use to develop reading proficiency and then conclude that the use of CALLA, the reading strategy instructions, is very significant and has a direct effect on young learners’ reading performance.